India: modernization and sustainable development - Rudenko, Elena I. (The New Research of Tuva, 2011)
The article deals with the issue of reconciling the socio-economic modernization priorities and sustainable development pur-poses in India with the accent on programs and concepts implemented during 1970-1980’s. The special attention is drawn towards the applica-tion of technical progress achievements in India with a view of envi-ronment protection, as well as environmental education. Also under consideration is the question of India’s international cooperation in the nature conservation sphere.